PENGELOLAAN KEBUN RAYA DAN KONTRIBUSI PEMERINTAH TERHADAP KONSERVASI TUMBUHAN DI KEBUN RAYA BOGOR - Lysna Lubis; Rasyidah Rasyidah (Jurnal Green Growth dan Manajemen Lingkungan, 2012)
ABSTRACTThe objective of the research is to determine the relationship between management of the botanical garden and government contribution toward the plan conservation. The research was conducted at Bogor Botanical Garden, West Java in 2010, with 35 samples as selected randomly. The research are follows : (1) there is positive correlation between management of the botanical garden toward the plan conservation; (2) there is positive correlation between government contribution toward the plan conservation, and (3) there is positive correlation between management of the botanical garden and government contribution toward the plan conservation. Based on the result of research can be use as and input for Bogor Botanical Garden and Indonesian Science Institute to increase plan conservation to prevent lost of biodiversity plan. 37